TEACHING CROSS-CULTURAL COMMUNICATION LITERATURE: A STUDY OF BHARATI MUKHERJEE'S THE TIGER'S DAUGHTER (International Journal of Food and Nutritional Sciences, 2022)
The cultural roles and adjectives in the quickly transforming world of reality enhance Oriental English writing. The Third-world authors of English-language fiction have grown emotionally attached to their homelands while still being outsiders in their nations. The primary subject of Bharati Mukherjee's writings is her conflicted relationship with both Eastern and Western traditions. She is both an Indian and an Indian Canadian. Due to the cultural clash between two various patterns and methods of living, an individual feels grief, annoyance, and loneliness. A person who leaves her/his own culture and enters another finds that the old and new values conflict since adjusting to and assimilating to the new ways of life is challenging. This paper demonstrates how understanding the distinctions between the native and assimilated cultures may help an Indian tax exile in Canada and America manage issues; Mukherjee uses cultural shock as the central theme of her story, The Tiger’s Daughter, the best example for cross cultural communication teaching.